Value Invariabilism and Two Distinctions in Value - Kopeikin, Zak A. (Ethical theory and moral practice, 2021)
Following Moore, value invariabilists deny that the intrinsic value of something can be affected by features extrinsic to it. The primary focuses of this paper are (i) to examine the invariabilistic thesis and expand upon how we ought to understand it, in light of contemporary axiological distinctions, and (ii) to argue that distinguishing between different kinds of invariabilism provides resources to undermine a prominent argument against variabilism. First, I use two contemporary axiological distinctions to clarify what kind of value the invariabilism debate concerns (final value). Then I show how the distinction between personal value and value simpliciter reveals different variabilistic theses, depending on what type of final value one thinks may be affected by extrinsic features. Using this insight, I challenge an argument for final value simpliciter invariabilism. Variabilists offer the example of the vicious being pleased as a counterexample to the claim that pleasure’s final value is invariant to contextual changes. The argument that I examine purports to show that this case actually supports invariabilism about pleasure’s final value simpliciter, because the best explanation for why the vicious being pleased is a fitting object of indignation is that the vicious person’s pleasure is finally valuable simpliciter. I argue that this argument fails because the vicious person’s pleasure being finally personally good for them better explains why an attitude of indignation is fitting. I address two objections and conclude with remarks about how my results might inform future research on value invariabilism.